Analisis Representasi Ideologi Media dalam Visual dan Lirik Video Musik Artificial Suicide oleh Bad Omens melalui Persepektif Louis Althusser - Anastasia Angelina Chandra; I Gusti Agung Alit Suryawati (GLOBAL SCIENTS PUBLISHER, 2026)
This article analyzes the representation of media ideology in the lyrics and music video visuals of Artifical Suicide by Bad Omens through the lens of Louis Althusser’s theory of ideology. Employing a qualitative interpretive approach with Roland Barthes’ semiotic analysis and critical disclosure analysis, this study reads the audio-visual text as a site where mechanisms of interpellation, Ideological State Apparatuses (ISA), and Baudrillard’s hyperreality operate simultaneously. Lyrical analysis demonstrates that the text interpellates listeners directly through rhetorical constructions that represent the internalization of dominant discourse as personal aspiration, most explicitly in the line “if I wanna be great, I don’t wanna be me” as verbalization of misrecognition. Visual analysis identifies the mise-en-scène of isolated space, latent RSA symbolism, the electrocution motif as a simulacrum loop, and gestures of self-violence as the materiality of the ideological process the lyrics describe verbally. The central finding reveals a structural paradox: a text that critiques the commodification of the subject operates entirely within the logic of the cultural industry it critiques, demonstrating that ideology provides no space outside itself from which the subject can stand free.